Influence of bentonite addition on parameters of fresh and hardened cement slurry - Kremieniewski, Marcin; Stryczek, Stanisław; Wiśniowski, Rafał; Rzepka, Marcin; Gonet, Andrzej (My University, 2017)
The recipe of cement slurry contains a number of additives and admixtures used for obtaining appropriate technological parameters. Some of these agents have a loose form and their density is higher or lower than that of working water, which may result in sedimentation of solid phase. For the sake of eliminating this effect, the viscosity of the working fluid should be increased to keep the fine solids over the entire volume of the slurry. This can be done with the use of appropriate high-molecular polymers. However, bearing in mind the cost of the polymers, bentonite is most frequently applied. Bentonite (montmorillonite) has a packet build and the resulting higher water-demand causes an increase of viscosity of working fluid. It is most frequently used to improve the sedimentation stability, though the presence of this additive is not neutral for the technological parameters of the slurry. During research works aimed at analyzing the influence of montmorillonite on the parameters of fresh and hardened cement slurry predefined quantities of bentonite were used in proportion to the working water. Reference recipes of slurries were worked out to trace the changes. The following properties of the slurry were defined: rheological parameters, filtration, thickening time, water settling, sedimentation stability. For hardened cement samples the bentonite addition was analyzed in view of its influence on the mechanical properties (compressive strength), physicochemical parameters (adhesiveness to steel pipes and adhesiveness to rock formation). Additionally, hardened cement slurry underwent analyses describing the microstructure of the sample porosity and permeability tests). For the sake of determining the influence of mineral additives on parameters of slurry and the hardened slurry there were performer tests for recipes of slurries to be used in wellbore conditions at temperature from 30°C to 90°C and pressure from 5 MPa to 35 MPa.
AGH Drilling, Oil, Gas
Keywords: cement slurries; bentonite